Implementasi Kurikulum Merdeka di Lombok NTB: Peluang, Tantangan dan Strategi - Zaelani; Fitriani, Iwan; Fattah, Abdul (Al-Riwayah : Jurnal Kependidikan, 2024)
Curriculum changes are an integral part of efforts to improve the quality of education. The "Kurikulum Merdeka" (Independent Curriculum) is the latest innovation implemented by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). This curriculum is designed to provide deeper learning experiences and focuses on strengthening students' competencies and character development. This study aims to analyze the implementation of the Kurikulum Merdeka, identify opportunities and challenges, and outline strategic steps to leverage opportunities and overcome challenges in implementing the Kurikulum Merdeka at Elementary School (SDN) 1 Sandik and Elementary School (SDN) 1 Meninting. This research employes a descriptive qualitative approach, using a case study methodology. Data collection procedures include interviews, observations, and documentation. The data analysis technique utilized was qualitative analysis. The results of this study indicate that: 1) the implementation of the Kurikulum Merdeka in both schools began with understanding government regulations, followed by preparing documents such as the Operational Curriculum of Educational Units, creating teaching modules, project modules, and assessments. 2) The opportunities available to both schools include policies from the central and local governments regarding funding for the Kurikulum Merdeka, and support from school principals, teachers, and parents to back various programs. However, challenges arise from human resources (educator competencies). 3) The strategic steps taken by both schools to leverage opportunities and address challenges include maximizing the school's learning community to discuss the Kurikulum Merdeka, organizing workshops, participating in webinars, and undergoing independent training via the "Platform Merdeka Mengajar" application.